Comparative Analysis of Ceramic Product Manufactured from Traditional Raw Materials and Local Raw Materials in Bangladesh - Mahmood, Abdullah Al; Rahman, Shamimur; Faruque, Omar; Kishor, Tanmoy (Engineering International, 2016)
Ceramic industries in Bangladesh are using raw materials imported from abroad. For this reason, manufacturing costs of the ceramic products are quite high. Now a day, the demand of the ceramic products in Bangladesh is very high. To reduce the cost of these ceramic products, different types of local clays can be used as raw materials with quartz and feldspar to manufacture ceramic ware, tile, and sanitary ware. In this research, locally available clay of nine different areas had been used to prepare the sample. Their physical and mechanical properties were tested and studied to evaluate the quality of the products. Khagrachari (canal) and Padma (north) clay have shown better physical and mechanical properties. This clay is suitable for the production of ceramic ware and Khagrachari (Hill) and Padma (South) clay for quality tiles. The compositions of locally available clays were determined using X-Ray Fluorescence (XRF). XRF analysis showed the presence of excess SiO2 content in the form of Silicate, Fe2O3, and TiO2 but the amount of Al2O3 in most of the compositions was also not up to the minimum level. Observing the physical and mechanical properties, it is found that the local clay materials are suitable to use in ceramic industries by replacing the imported/traditional clay to reduce cost and make a perfect use of our natural resources.
Keywords: Clay; porosity; compressive strength; ceramic products